Effect of a Traditional Chinese Herbal Medicine Formulation on Cell Survival and Apoptosis of MPP+-Treated MES 23.5 Dopaminergic Cells - Shuifen Ye; Ho Kee Koon; Wen Fan; Yihui Xu; Wei Wei; Chuanshan Xu; Jing Cai (Parkinson's Disease)
Progressive degeneration of dopaminergic neurons in the substantia nigra (SN) is implicated in Parkinson’s disease (PD). The efficacy of these currently used drugs is limited while traditional Chinese medicine (TCM) has been used in the management of neurodegenerative diseases for many years. This study was designed to evaluate the effect of a modified traditional Chinese herbal medicine decoction, Cong Rong Jing (CRJ), on cell survival and apoptosis of 1-methyl-4-phenylpyridinium- (MPP+-) treated MES23.5 dopaminergic cells. CRJ was prepared as a decoction from three Chinese herbs, namely, Herba Cistanches, Herba Epimedii, and Rhizoma Polygonati. We reported here that CRJ significantly enhanced the cell survival of MES23.5 cells after the exposure of MPP+ and inhibited the production of intracellular reactive oxygen species (ROS) induced by MPP+. CRJ also prevented the MPP+-treated MES23.5 cells from apoptosis by reducing the externalization of phosphatidylserine and enhancing the Bcl-2/Bax protein expression ratio. Signaling proteins such as JAK2, STAT3, and ERK1/2 were also involved in the action of CRJ. Taken together, these results provide a preliminary mechanism to support clinical application of the TCM formulation in PD and possibly other neurodegenerative diseases associated with ROS injury and apoptosis.